Implementation of Audit Standards in General Audits for MSMEs: Challenges and Solutions in Financial Statement Preparation - Zefanya Ieremia Delpiero Siringoringo; Karsam Karsam (Journal Research of Social Science, Economics, and Management, 2025)
This research aims to analyze the effect of audit standard implementation, accounting literacy, cloud-based accounting technology adoption, training and mentoring, and internal control on the quality and auditability of financial statements of Micro, Small, and Medium Enterprises (MSMEs) in East Java. The research employed a quantitative approach with an explanatory design. The sample consisted of 107 MSME owners/managers selected through purposive sampling. Data were collected using a structured questionnaire and analyzed using multiple linear regression with SPSS, including classical assumption tests, F-tests, and t-tests. The results show that simultaneously, all five independent variables have a significant effect on financial statement quality (F = 58.605; p = 0.000) with an R² contribution of 0.744. Partially, the adoption of cloud-based accounting technology (p = 0.018) and internal control (p < 0.001; Beta = 0.715) have a positive and significant effect, with internal control being the most dominant factor. In contrast, audit standard implementation (p = 0.268), accounting literacy (p = 0.788), and training and mentoring (p = 0.532) show no significant effect. These findings highlight that improving the quality of MSME financial statements is more influenced by technical factors and operational controls rather than merely knowledge or the availability of standards. Recommendations include strengthening internal control, adopting cloud-based accounting technology, and implementing practice-based mentoring to enhance the accountability and auditability of MSME financial statements.